Sistem Pendukung Keputusan untuk Pemilihan Rekomendasi Desain Kacamata Terbaik Menggunakan Metode SAW - Longse, Maylson; Imam Suharjo (STMIK Budi Darma, 2024)
In an era where the variety of eyewear designs and the development of various fashion trends, often makes it difficult for consumers to choose the best eyewear design to use so that a system is needed for this. Decision support systems are an effective solution in helping make this decision. This research uses the Simple Additive Weighting method to help in choosing eyewear designs based on several criteria such as design, material, price, lens type and brand. The Simple Additive Weighting method allows the calculation of the score of each selected criterion, assigns the appropriate weights, and produces eyewear recommendations that best suit customer preferences and needs. The use of Decision Support Systems is expected to not only simplify the process of selecting glasses, but also increase user satisfaction with the selected product that matches their expectations. This research aims to provide an understanding of the use of decision support systems applied to the optical industry to provide good service to customers. The comparison results of 30 data taken from 3 customers to test the system show a similarity of 86% in the tabel of test results of the method (SAW).So that the decision support system with the simple Addiptive Weighting method is the right system for selecting eyewear designs using the saw method based on the criteria set. Selection of glasses with the Supor brand FF151 series lens size 59mm bridge width 16mm stalk length 152mm with titanium material at a price of Rp.450,000 and the type of transition lens is the best choice in choosing the best eyewear design.